Implementasi Metode RGB To HSV pada Aplikasi Pengenalan Mata Uang Kertas Berbasis Android untuk Tuna Netra - Julian Fuad Fauzi; Herman Tolle; Ratih Kartika Dewi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
HSV Digital Imagery defines colors in Hue terminology (Color Actually), Saturation (Color Purity) and Value (Color Brightness) The advantage of HSV is that there are the same colors as those captured by the human senses. While the color of other models such as RGB formed a mixture of primary colors. Applications of mobile paper based paper detection Android, so users can easily run this application anywhere and anytime with mobile users. This is where the discussion is about building an app for a currency value detection system that blind users can use to detect the value of a paper currency. Detection is performed on Indonesian banknotes of 1000, 2000,, 5000, 10000, 20000, 50000, and 100000. The system gives a sound output conclusion in Bahasa Indonesia about the value of banknotes Digital image using RGB2HSV method can run well and able to classify in accordance with the results of design and in testing the test data obtained the conclusion that the RGB2HSV method can provide information about the distance of the image with the accuration rate of 87%, precision of 89%, and the recall of 94%.